ANALISIS KEMAMPUAN MEMBAYAR TARIF ANGKUTAN KOTA (Studi Kasus Pengguna Jasa Angkutan Kota pada Empat Kecamatan di Kota Semarang) - Wicaksono, Y I; Riyanto, Bambang; Kusumastuti, Dianita Ratna (Department of Civil Engineering, 2006)
ABSTRACT To determine the fare of city transport, the local government as a regulator has to consider two different interests those are interest of the operator and interest of the user. The operator wishes the fare would give high profit, while the user affected wishes the cheapest fare. The factors to the fare rate are vehicle operation cost, and ability to pay of the users. This study is focussed as the discussion of the ability to pay of the users.Two approaches were used to find and the ability to pay of users those are the ability based on user perception (willingness to pay) and ability based on budget allocation for transport (ability to pay).The factors used to determine the Ability To Pay and Willingness To Pay are house size, family income, transportation needs, total transportation cost and trip distance. Data was collected by questioner and interviewing the respondent at four kecamatan i.e. Gayamsari, South Semarang, East Semarang and Central Semarang. It was found the public transport which was dominated by man, of 20 – 50 year old, and elementary education level. Keywords : Willingness to pay, ability to pay